Diversity of Quantitative and Qualitative Characters of Rice Grain from Riau Province, Indonesia - Nurul Hidayatun; Devi Ramadyanti; Dodin Koswanuddin; Etyn Yunita (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumberdaya Genetik Pertanian, 2021)
Rice is grown in almost all regions in Indonesia, including Riau Province, as a staple food. Although rice is the most widely grown food crop in comparison to other crops, rice production from this region has not been able to meet the needs of the Riau population. To meet the needs of rice, the people of Riau still have to bring it from other regions. Riau Province has a large collection of diverse rice germplasm for food self-sufficiency. Several rice accessions from the area have been collected and conserved in the Genebank of the Indonesian Agency for Agricultural Research and Development (IAARD), located at Indonesian Center for Agricultural Biotechnology and Genetic Resources Research and Development (ICABIOGRAD). This study was intended to assess the diversity of rice from Riau Province based on the grain characteristics. A total of 25 rice accessions from Riau which were conserved in the IAARD-ICABIOGRAD Genebank were examined. Grain length, shape, color, and other grain-related characters were observed following the international standard descriptors for rice by IRRI and IBPGR. While the thousand-grain weight was measured using the standardized operational procedure from ISTA. The grain diversity was analyzed using the NTSYS-pc software version 2.2. The average of length, width, and thickness of the unhulled paddy was measured at 7.9, 3.0, and 1.9 mm, respectively. The weight of 1,000 grains ranged from 20.37 to 25.67 with an average of 23.02 g. Most of the accessions had a brown furrow or spot on straw background lemma-palea, with a straw apiculus a medium-sized sterile lemma, and were awnless. The majority of the rice grain was medium size, measuring 5.24 mm in length and 2.24 mm in width. White grain makes up the majority of the accessions. Accessions from Riau can be divided into five groups based on the seven characteristics of rice grains. Those groupings were unrelated to the district from which the accessions were obtained, illustrating the beyond boundaries of germplasm distribution and transfer of germplasm within this district.